2015
DOI: 10.1101/mcs.a000547
|View full text |Cite
|
Sign up to set email alerts
|

FOXP2 gene deletion and infant feeding difficulties: a case report

Abstract: Forkhead box protein P2 (FOXP2) is a well-studied gene known to play an essential role in normal speech development. Deletions in the gene have been shown to result in developmental speech disorders and regulatory disruption of downstream gene targets associated with common forms of language impairments. Despite similarities in motor planning and execution between speech development and oral feeding competence, there have been no reports to date linking deletions within the FOXP2 gene to oral feeding impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…Human and animal studies confirmed that FOXP2 plays a role in the function and development of motor skills and vocal behavior-related neuronal circuits [26]. Abnormalities of FOXP2 are associated with speech-language delay and language disorders such as in spelling and reading [6,24,27,28] as well as for the application of imaging genetics in dyslexia study [29]. The same neural paths as language are involved in feeding and sucking behavior as one of the earliest manifestations of newborn motor control [20].…”
Section: Foxp2 Gene and Oral-motor Abilitymentioning
confidence: 87%
See 1 more Smart Citation
“…Human and animal studies confirmed that FOXP2 plays a role in the function and development of motor skills and vocal behavior-related neuronal circuits [26]. Abnormalities of FOXP2 are associated with speech-language delay and language disorders such as in spelling and reading [6,24,27,28] as well as for the application of imaging genetics in dyslexia study [29]. The same neural paths as language are involved in feeding and sucking behavior as one of the earliest manifestations of newborn motor control [20].…”
Section: Foxp2 Gene and Oral-motor Abilitymentioning
confidence: 87%
“…Factors contributing to feeding difficulties in premature infants include impaired oral structure-function, impaired sucking pattern, impaired sucking-swallowing-breathing coordination and transition to oral feeding [5]. A prior study revealed that the expression of forkhead box protein 2 (FOXP2) gene in saliva was Review Article linked to successful oral feeding in preterm neonates [6]. However, there has been no study discussing comprehensively about the oral-motor abilities, such as oral feeding, suckingswallowing-breathing coordination and language development, that are related to FOXP2 gene, particularly in the preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Dès l'enfance, cette mutation est corrélée à l'incapacité à contrôler les mouvements moteurs faciaux et buccaux lors de l'émission du langage expressif et réceptif. Elle est associée à l'incoordination de l'ingestion alimentaire orale qui se traduit par des fausses routes respiratoires [31]. Les études par imagerie fonctionnelle cérébrale des patients de la famille KE, ainsi que d'autres sujets atteints de façon similaire, ont révélé une réduction des structures tissulaires neurales impliquées dans la genèse du langage, comme l'aire de Broca, le noyau caudé, le striatum et le cervelet [32].…”
Section: Manger Respirer Crier Puis Parler Et Chanter : Une Filiation Unique De L'évolutionunclassified
“…Le centre moteur frontal pneumo-laryngopharyngo-glosso-buccal du langage de Broca et le gène FOXP2 [8,[28][29][30][31][32] premiers tétrapodes dentés encore muni de branchies, le chaînon manquant avec les poissons dont les descendants sont aujourd'hui les dipneustes 1 australiens et les coelacanthes 2 [16,17]. À partir du Dévonien, les tétrapodes et vertébrés terrestres se sont diversifiés phylétiquement 3 (en amphibiens, reptiles, oiseaux, et en mammifères) [2, [10][11][12][13][14][15].…”
unclassified
“…In initial studies, the combined salivary expression profile of these biomarkers was shown to be up to 78% accurate in predicting mature oral feeding skills in the newborn. In addition, our laboratory has been the first to link expression levels of a well-described speech–language gene, FOXP2 , to oral feeding success in the newborn ( 54 , 55 ). These experiments have laid the foundation for future studies to non-invasively explore developmental biology in our youngest patients and offer caregivers an enormous opportunity to utilize salivary transcriptomics to further explore, diagnose, and potentially prevent other areas of neonatal pathology where disrupted development results in unique and often life-threatening diseases including bronchopulmonary dysplasia, necrotizing enterocolitis (NEC), or retinopathy of prematurity.…”
Section: Salivary “Omics”mentioning
confidence: 99%